Malignant Hyperthermia and Gene Polymorphisms Related to Inhaled Anesthesia Drug Response - Vu Thi Thu Hang; Nguyen Thi Thu Mau; Nguyen Tran Thuy; Le Ngoc Thanh; Nguyen Thi Hong Nhung; Dinh Doan Long; Nguyen Thi Thu Hoai; Vu Thi Thom (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
Malignant hyperthermia (MH) is a clinical response happened to patient who is sensitive with inhaled anesthesia drug that could cause suddently death. Many previous studies showed that malignant hyperthermia strongly related to genetic background of patients including RYR1, CACNA1S or STAC3 gene polymorphisms. With the development of high technology such as next generation sequencing, scientists found that 37 to 86 percents of MH cases had RYR1 mutations and approximately 1 percent of those had CACNA1S mutations. Gene analysis testing was recommended to apply for patient with MH medical history or MH patient’s family relations. Keywords Malignant hyperthermia, inhaled anesthesia, RYR1, CACNA1S, STAC3. References [1] G. Torri, Inhalation anesthetics: a review, Minerva Anestesiologica 76 (2010) 215–228. [2] N. Kassiri, S. Ardehali, F. Rashidi, S. Hashemian, Inhalational anesthetics agents: The pharmacokinetic, pharmacodynamics, and their effects on human body, Biomed. Biotechnol. Res. J. BBRJ 2 (2018) 173. https://doi.org/10.4103/bbrj.bbrj_6618.[3] H. Rosenberg, N. Sambuughin, S. Riazi, R. Dirksen, Malignant Hyperthermia Susceptibility, in: M.P. Adam, H.H. Ardinger, R.A. Pagon, S.E. Wallace, L.J. Bean, K. Stephens, A. Amemiya (Eds.), GeneReviews, University of Washington, Seattle, Seattle (WA), 19932020. http://www.ncbi.nlm.nih.gov/books/NBK1146/ (accessed February 2, 2020).[4] H. Rosenberg, N. Pollock, A. Schiemann, T. Bulger, K. Stowell, Malignant hyperthermia: a review, Orphanet J. Rare Dis 10 (2015) 93. https://doi.org/10.1186/s13023-015-0310-1.[5] D. Carpenter, C. Ringrose, V. Leo, A. Morris, R.L. Robinson, P.J. Halsall, P.M. Hopkins, M.-A. Shaw, The role of CACNA1S in predisposition to malignant hyperthermia, BMC Med. Genet 10 (2009) 104. https://doi.org/10.1186/1471-2350-10-104.[6] S. Riazi, N. Kraeva, P.M. Hopkins, Updated guide for the management of malignant hyperthermia, Can. J. Anaesth. J. Can. Anesth 65 (2018) 709–721. https://doi.org/10.1007/s12630-018-1108-0.[7] S. Riazi, N. Kraeva, P.M. Hopkins, Malignant Hyperthermia in the Post-Genomics Era: New Perspectives on an Old Concept, Anesthesiology 128 (2018) 168–180. https://doi.org/10.1097/ALN.0000000000001878.[8] [D.M. Miller, C. Daly, E.M. Aboelsaod, L. Gardner, S.J. Hobson, K. Riasat, S. Shepherd, R.L. Robinson, J.G. Bilmen, P.K. Gupta, M.-A. Shaw, P.M. Hopkins, Genetic epidemiology of malignant hyperthermia in the UK, BJA Br. J. Anaesth 121 (2018) 944–952. https://doi.org/10.1016/j.bja.2018.06.028.[9] T.A. Beam, E.F. Loudermilk, D.F. Kisor, Pharmacogenetics and pathophysiology of CACNA1S mutations in malignant hyperthermia, Physiol. Genomics 49 (2017) 81–87. https://doi.org/10.1152/physiolgenomics.00126.2016.[10] I.T. Zaharieva, A. Sarkozy, P. Munot, A. Manzur, G. O’Grady, J. Rendu, E. Malfatti, H. Amthor, L. Servais, J.A. Urtizberea, O.A. Neto, E. Zanoteli, S. Donkervoort, J. Taylor, J. Dixon, G. Poke, A.R. Foley, C. Holmes, G. Williams, M. Holder, S. Yum, L. Medne, S. Quijano-Roy, N.B. Romero, J. Fauré, L. Feng, L. Bastaki, M.R. Davis, R. Phadke, C.A. Sewry, C.G. Bönnemann, H. Jungbluth, C. Bachmann, S. Treves, F. Muntoni, STAC3 variants cause a congenital myopathy with distinctive dysmorphic features and malignant hyperthermia susceptibility, Hum. Mutat 39 (2018) 1980–1994. https://doi.org/10.1002/humu.23635.[11] A.F. Dulhunty, The voltage-activation of contraction in skeletal muscle, Prog. Biophys. Mol. Biol 57 (1992) 181–223. https://doi.org/10.1016/0079-6107(92)90024-Z.[12] C. Franzini-Armstrong, A.O. Jorgensen, Structure and Development of E-C Coupling Units in Skeletal Muscle, Annu. Rev. Physiol 56 (1994) 509–534. https://doi.org/10.1146/annurev.ph.56.030194.002453.[13] D.H. MacLennan, M. Abu-Abed, C. Kang, Structure-function relationships in Ca(2+) cycling proteins, J. Mol. Cell. Cardiol 34 (2002) 897–918. https://doi.org/10.1006/jmcc.2002.2031.[14] H. Rosenberg, M. Davis, D. James, N. Pollock, K. Stowell, Malignant hyperthermia, Orphanet J. Rare Dis 2 (2007) 21. https://doi.org/10.1186/1750-1172-2-21.[15] S.M. Karan, F. Crowl, S.M. Muldoon, Malignant hyperthermia masked by capnographic monitoring, Anesth. Analg 78 (1994) 590–592. https://doi.org/10.1213/00000539-199403000-00029.[16] M.G. Larach, G.A. Gronert, G.C. Allen, B.W. Brandom, E.B. Lehman, Clinical presentation, treatment, and complications of malignant hyperthermia in North America from 1987 to 2006, Anesth. Analg 110 (2010) 498–507. https://doi.org/10.1213/ANE.0b013e3181c6b9b2.[17] M.G. Larach, A.R. Localio, G.C. Allen, M.A. Denborough, F.R. Ellis, G.A. Gronert, R.F. Kaplan, S.M. Muldoon, T.E. Nelson, H. Ording, H. Rosenberg, B.E. Waud, D.J. Wedel, A Clinical Grading Scale to Predict Malignant Hyperthermia Susceptibility, Anesthesiology 80 (1994) 771–779. https://doi.org/10.1097/00000542-199404000-00008.[18] D. Schneiderbanger, S. Johannsen, N. Roewer, F. Schuster, Management of malignant hyperthermia: diagnosis and treatment, Ther. Clin. Risk Manag 10 (2014) 355–362. https://doi.org/10.2147/TCRM.S47632.[19] R. Robinson, D. Carpenter, M.-A. Shaw, J. Halsall, P. Hopkins, Mutations in RYR1 in malignant hyperthermia and central core disease, Hum. Mutat 27 (2006) 977–989. https://doi.org/10.1002/humu.20356.[20] M.L. Alvarellos, R.M. Krauss, R.A. Wilke, R.B. Altman, T.E. Klein, PharmGKB summary: very important pharmacogene information for RYR1, Pharmacogenet. Genomics 26 (2016) 138–144. https://doi.org/10.1097/FPC.0000000000000198.[21] A. Merritt, P. Booms, M.-A. Shaw, D.M. Miller, C. Daly, J.G. Bilmen, K.M. Stowell, P.D. Allen, D.S. Steele, P.M. Hopkins, Assessing the pathogenicity of RYR1 variants in malignant hyperthermia, BJA Br. J. Anaesth 118 (2017) 533–543. https://doi.org/10.1093/bja/aex042.[22] P.M. Hopkins, H. Rüffert, M.M. Snoeck, T. Girard, K.P.E. Glahn, F.R. Ellis, C.R. Müller, A. Urwyler, European Malignant Hyperthermia Group, European Malignant Hyperthermia Group guidelines for investigation of malignant hyperthermia susceptibility, Br. J. Anaesth 115 (2015) 531–539. https://doi.org/10.1093/bja/aev225.[23] N.T. Thuy, L.N. Thanh, N.T.T. Mau, N.H. Hoang, N.T.K. Lien, D.D. Long, N.T. Bình, D.A. Tien, N.C. Huu, N.T. Hieu, P.T.H. Nhung, V.T. Thom, Whole exome sequencing revealed a pathogenic variant in a gene related to malignant hyperthermia in a Vietnamese cardiac surgical patient: A case report, Ann. Med. Surg 48 (2019) 88–90. https://doi.org/10.1016/j.amsu.2019.10.030.[24] B. Neuhuber, U. Gerster, F. Döring, H. Glossmann, T. Tanabe, B.E. Flucher, Association of calcium channel α1S and β1a subunits is required for the targeting of β1a but not of α1S into skeletal muscle triads, Proc. Natl. Acad. Sci. U. S. A 95 (1998) 5015–5020. https://doi.org/10.1073/pnas.95.9.5015.[25] M. Whirl-Carrillo, E.M. McDonagh, J.M. Hebert, L. Gong, K. Sangkuhl, C.F. Thorn, R.B. Altman, T.E. Klein, Pharmacogenomics Knowledge for Personalized Medicine, Clin. Pharmacol. Ther 92 (2012) 414–417. https://doi.org/10.1038/clpt.2012.96.[26] N. Monnier, V. Procaccio, P. Stieglitz, J. Lunardi, Malignant-hyperthermia susceptibility is associated with a mutation of the alpha 1-subunit of the human dihydropyridine-sensitive L-type voltage-dependent calcium-channel receptor in skeletal muscle, Am. J. Hum. Genet 60 (1997) 1316–1325 . https://doi.org/10.1086/515454.[27] S.L. Stewart, K. Hogan, H. Rosenberg, J.E. Fletcher, Identification of the Arg1086His mutation in the alpha subunit of the voltage-dependent calcium channel (CACNA1S) in a North American family with malignant hyperthermia, Clin. Genet 59 (2001) 178–184. https://doi.org/10.1034/j.1399 0004.2001.590306.x.[28] P.J. Toppin, T.T. Chandy, A. Ghanekar, N. Kraeva, W.S. Beattie, S. Riazi, A report of fulminant malignant hyperthermia in a patient with a novel mutation of the CACNA1S gene, Can. J. Anaesth. J. Can. Anesth 57 (2010) 689–693. https://doi.org/10.1007/s12630-010-9314-4.[29] E.J. Horstick, J.W. Linsley, J.J. Dowling, M.A. Hauser, K.K. McDonald, A. Ashley-Koch, L. Saint-Amant, A. Satish, W.W. Cui, W. Zhou, S.M. Sprague, D.S. Stamm, C.M. Powell, M.C. Speer, C. Franzini-Armstrong, H. Hirata, J.Y. Kuwada, Stac3 is a component of the excitation-contraction coupling machinery and mutated in Native American myopathy, Nat. Commun 4 (2013) 1952. https://doi.org/10.1038/ncomms2952.[30] D.S. Stamm, A.S. Aylsworth, J.M. Stajich, S.G. Kahler, L.B. Thorne, M.C. Speer, C.M. Powell, Native American myopathy: Congenital myopathy with cleft palate, skeletal anomalies, and susceptibility to malignant hyperthermia, Am. J. Med. Genet. A 146A (2008) 1832–1841. https://doi.org/10.1002/ajmg.a.32370.[31] A. Polster, B.R. Nelson, S. Papadopoulos, E.N. Olson, K.G. Beam, Stac proteins associate with the critical domain for excitation–contraction coupling in the II–III loop of CaV1.1, J. Gen. Physiol 150 (2018) 613–624. https://doi.org/10.1085/jgp.201711917.[32] S.M. Wong King Yuen, M. Campiglio, C.-C. Tung, B.E. Flucher, F. Van Petegem, Structural insights into binding of STAC proteins to voltage-gated calcium channels, Proc. Natl. Acad. Sci 114 (2017) E9520–E9528. https://doi.org/10.1073/pnas.1708852114.[33] M. Grabner, R.T. Dirksen, N. Suda, K.G. Beam, The II-III loop of the skeletal muscle dihydropyridine receptor is responsible for the Bi-directional coupling with the ryanodine receptor, J. Biol. Chem 274 (1999) 21913–21919. https://doi.org/10.1074/jbc.274.31.21913.[34] J. Nakai, T. Tanabe, T. Konno, B. Adams, K.G. Beam, Localization in the II-III loop of the dihydropyridine receptor of a sequence critical for excitation-contraction coupling, J. Biol. Chem 273 (1998) 24983–24986. https://doi.org/10.1074/jbc.273.39.24983.[35] C.J. Morton, I.D. Campbell, SH3 domains. Molecular “Velcro,” Curr. Biol. CB 4 (1994) 615–617. https://doi.org/10.1016/s0960-9822(00)00134-2.[36] A. Zafra-Ruano, I. Luque, Interfacial water molecules in SH3 interactions: Getting the full picture on polyproline recognition by protein-protein interaction domains, FEBS Lett 586 (2012) 2619–2630. https://doi.org/10.1016/j.febslet.2012.04.057.